TRADITIONAL STORM RUNOFF MANAGEMENT FOR IRRIGATING MEADOWS IN MONTEAGUDO DEL CASTILLO (TERUEL) - Pérez Cueva, Alejandro J.; Fansa Saleh, Ghaleb (Geographicalia, 2021)
Monteagudo del Castillo (Teruel) is near the pole of maximum violent storms of the Iberian Peninsula. The pluviometric contribution of these storms is capable of reversing the usual seasonal regime of the Mediterranean climate, with summer as the rainiest season. Here the traditional management of the stream in two basins of the municipal area is studied, from the double perspective risk/resource: control of erosion and use of the stream to irrigate meadows. To manage the concentrated stream of the storms, the drainage network has been modified through collecting and/or evacuating channels and the rectification of the natural hydrographic network. The derivation channels allow the existence of meadows for cattle with rainfall of around 430 mm/year. The drainage network is reconstructed through field work, photointerpretation and LIDAR data, to conceptualize the channel types, interpret the anthropic network and determine management strategies.
Keywords: Thunderstorms; concentrated runoff; water harvesting; Alto Alfambra; anthropic drainage network